Sport and National Identities - Dolan, Paddy; Connolly, John (Taylor & Francis, 2017)
While globalisation has undoubtedly occurred in many social fields, in sport the importance of 'the nation' has remained. This book examines the continuing but contested relevance of national identities in sport within the context of globalising forces. Including case studies from around the world, it considers the significance of sport in divided societies, former global empires and aspirational nations within federal states. Each chapter looks at sport not only as a reflection of national rivalries but also as a changing cultural tradition that facilitates the reimagining of borders, boundaries and identities. The book questions how these national, state and global identifications are invoked through sporting structures and practices, both in the past and the present. Truly international in perspective, it features case studies from across Europe, the UK, the USA and China and touches on the topics of race, religion, terrorism, separatism, nationalism and militarism. Sport and National Identities: Globalisation and Conflict is fascinating reading for anyone with an interest in the sociology of sport or the relationship between sport, politics, geography and history.